Macronutrients omission in development of african mahogany seedlings - Vieira, Cristiane Ramos; Weber, Oscarlina Lúcia dos Santos; Scaramuzza, José Fernando (Revista Ecologia e Nutrição Florestal - ENFLO, 2015)
The study aimed to identify the visual symptoms of macronutrients deficiencies, growth and the most absorbed by african mahogany (Khaya anthotheca Welv.) seedlings, submitted to macronutrients omission. The seedlings were grown in tubes containing sand, then were transplanted to PVC tube with sand and submitted for 15 days to complete nutrient solution. Then, were submitted for 90 days to complete nutrient solutions (macro and micronutrients) and omission of N, P, K, Ca, Mg and S, constituting a randomized design with seven treatments and four replications. The symptoms of deficiency were described each five days. At the end of the experiment, the seedlings were evaluated to height, diameter, dry biomass, Dickson quality index and concentration of macronutrients. In this context, the growth and quality of Khaya anthotheca was more limited by N, K and S omissions that were the most absorbed by the seedlings on complete solutions.